CURRENT PROBLEMS OF AGRICULTURAL PRODUCTION UNDER THE INTRODUCTION OF MARKET APPEALS OF AGRICULTURAL LAND - Sakharchenko, V.I. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
The purpose of the study is to identify the impact of the agricultural land market (ALM) on agricultural production and to find ways to solve problems related to its implementation. The article defines that the land reform in Ukraine should be carried out with a focus on increasing the efficiency of the use of ALMs as the main means of agricultural production. In this regard, the circle of problems of agricultural production is outlined, which in the conditions of market circulation of ALMs are opened by new parties, and therefore need its own solution through proper institutional support and a number of organizational and economic measures. Actual problems of agricultural production are analyzed, in particular: parcelerization (grinding) of land massifs; formation of irrational land use structure; monospecialization of agricultural holdings; aggravated agricultural producers lack of working and fixed assets and investment resources; increasing tax pressure on agricultural producers; reducing the "resilience threshold" and increasing the risk of bankruptcy of agricultural producers. Based on the analysis and taking into account foreign experience, the ways of solving these problemsare outlined